Added Value of an Anti-Ebola Serology for the Management of Clinically Suspected Ebola Virus Disease Patients Discharged as Negative in an Epidemic Context. (18th February 2022) - Nkuba-Ndaye, Antoine; Mukadi-Bamuleka, Daniel; Bulabula-Penge, Junior; Thaurignac, Guillaume; Edidi-Atani, François; Mambu-Mbika, Fabrice; Danga-Yema, Bernice; Matondo-Kuamfumu, Meris; Kinganda-Lusamaki, Eddy; Bisento, Nella; Lumembe-Numbi, Raphaël; Kabamba-Lungenyi, Gabriel; et al.
Abstract: Background: Survivors from Ebola virus disease (EVD) may be at the origin of EVD resurgence. Methods: Simultaneous reactivity to at least 2 Ebola virus or Zaire ebolavirus (EBOV) antigens was detected in 11 of 488 (2.3%; 95% confidence interval [CI], 1.1–4.0) suspected EVD patients who were discharged as negative after 2 consecutive negative tests during the 10th Ebola outbreak in the Democratic Republic of the Congo. Results: After extrapolating the total number of individuals discharged as negative during the entire outbreak, we estimated a total of 1314 additional missed Ebola cases. Conclusions: These findings emphasize the usefulness of an EBOV serology analysis and the importance of extending epidemic surveillance to clinically suspected cases who were discharged as negative. Abstract : In clinically suspected EVD patients, EVD may be missed and inadvertently cause EBOV resurgence. Thus, surveillance during and after outbreaks should be extended to EBOV household contacts and to patients discharged as negative with an accurate serologic assay.